An exploration of doping-related perceptions and knowledge of disabled elite athletes in the UK and Austria. (January 2022) - Weber, Kathrin; Patterson, Laurie B.; Blank, Cornelia
Abstract: Introduction: Compared to anti-doping research in Olympic sport, the issue of doping is under-researched and poorly understood in Paralympic sport. However, with the growth of the Paralympic Games and the increased number of disabled elite athletes, the number of doping controls and doping cases has also increased. Therefore, there is a need to address the dearth of evidence in disabled sport contexts and develop an understanding of disabled elite athletes' perceptions, reasons and knowledge related to doping to ensure appropriate policy and programmes are implemented. Method: Sixteen disabled elite athletes from Austria (n = 9) and the UK (n = 7) participated in semi-structured interviews. Data were analysed using inductive reflexive thematic analysis (Braun & Clarke, 2019a). Findings: Four themes were generated during the analysis. The first showed that athletes perceive doping to be a well-known and wide-spread issue in Paralympic sport. The second theme illustrated that disabled elite athletes are exposed to extreme pressure (e.g., to earn money), which they state poses a risk for using prohibited methods and/or substances. Thirdly, athletes suggested that there are several ways to cheat if someone would like to find 'loopholes' (e.g., misuse of Therapeutic Use Exemptions) in the current anti-doping system, which they reported only works partially. Lastly, although it is not officially named as an anti-doping rule violation, athletes proposed cheating on classification as a form of doping – and the greatest threat to the integrity of disabled sport. Conclusions: For the first time, the current study shows that doping in the context of disabled elite sport likely stems from only a few main factors; a perception of pressure and faults in the anti-doping system. To address these risks, prize money could be distributed more broadly, the TUE process and classification system should be more closely scrutinised, and targeted anti-doping education that addresses the main risk factors in disabled elite sport should be provided for all athletes and their support team worldwide. Highlights: Doping seems to be a widespread and well-known issue within Paralympic sport. Pressure to earn money and/or meet stakeholder demands increases doping risk. Various loopholes in the anti-doping system makes doping a considerable solution. Classification cheating is seen as a form of doping and greatest integrity issue.